Odpowiedzi

Najlepsza Odpowiedź!
2010-03-18T15:31:32+01:00
-17x - 15x - 13x - 10x + 10x + 13x + 15x + 17x = 0
-10x - 8x - 6x - 2x + 2x + 6x + 8x=-10x
-123x - 55x - 39x + 23x - 155x + 239x = -110x
439x - 427x + 369x - 357x + 229x - 217x =36x
1 4 1
2010-03-18T15:36:23+01:00
-17x-15x-13x-10x+10x+13x+15x+17x=-17x+17x+15x-15x+13x-13x+10x-10x=0+0+0+0=0

-10x-8x-6x-2x+2x+6x+8x=8x-8x+2x-2x+6x-6x-10x=0+0+0-10=-10x

-123x-55x-39x+23x-155x+239x=-123x+23x+239x-39x+155x-55x=100x+200x+100x=400x

439x-427x+369x-357x+229x-217x=
2010-03-18T15:36:59+01:00
-17x - 15x - 13x - 10x + 10x + 13x + 15x + 17x = 0
-10x - 8x - 6x - 2x + 2x + 6x + 8x = -10x
-123x - 55x - 39x + 23x - 155x + 239x =-178x-16x-84x=-278x
439x - 427x + 369x - 357x + 229x - 217x =12x+12x+12x=36x